Gas cylinders. Design, construction and testing of refillable seamless steel gas cylinders and tubes. Quenched and tempered steel cylinders and tubes with tensile strength greater than or equal to 1 100 MPa Part 2, (25th October 2019) - British Standards Institution,
No abstract available